2022
DOI: 10.1111/sed.13040
|View full text |Cite
|
Sign up to set email alerts
|

Controls on the morphology of braided rivers and braid bars: An empirical characterization of numerical models

Abstract: Braided rivers exhibit highly variable morphologies, morphodynamic behaviours and resulting depositional records. To evaluate relationships between characteristics of braided-river channel belts and river depth, water discharge and streambed gradient, 39 numerical modelling experiments were conducted with the software Delft3D to simulate braided-river evolution under a broad range of boundary conditions. Data from model outputs were integrated with observations from 63 natural braided rivers differing with res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
(127 reference statements)
0
4
0
Order By: Relevance
“…Details about paleochannel movements are recorded in the geometry, arrangement and preservation character of bar deposits in ancient channel fills (e.g., Colombera et al, 2017;Durkin et al, 2017Durkin et al, , 2018Chamberlin and Hajek, 2019) and are useful in answering outstanding questions about channel mobility (e.g. Mohrig et al, 2000;Wickert et al, 2013;Sahoo et al, 2020), channel planform (e.g., Gibling, 2006;Hartley et al, 2015), and river response to flow variability (e.g., Sambrook Smith et al, 2010;Nicholas et al, 2016;Li et al, 2023). Additionally, the height of fully preserved clinoforms (Figure 1) is a proxy for paleo-flow depth (Mohrig et al, 2000;Hajek and Heller, 2012)-an essential parameter in reconstructing the paleohydraulic conditions of ancient rivers (e.g., Hartley et al, 2015;Mahon and McElroy, 2018;Lyster et al, 2021Lyster et al, , 2022Hartley and Owen, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Details about paleochannel movements are recorded in the geometry, arrangement and preservation character of bar deposits in ancient channel fills (e.g., Colombera et al, 2017;Durkin et al, 2017Durkin et al, , 2018Chamberlin and Hajek, 2019) and are useful in answering outstanding questions about channel mobility (e.g. Mohrig et al, 2000;Wickert et al, 2013;Sahoo et al, 2020), channel planform (e.g., Gibling, 2006;Hartley et al, 2015), and river response to flow variability (e.g., Sambrook Smith et al, 2010;Nicholas et al, 2016;Li et al, 2023). Additionally, the height of fully preserved clinoforms (Figure 1) is a proxy for paleo-flow depth (Mohrig et al, 2000;Hajek and Heller, 2012)-an essential parameter in reconstructing the paleohydraulic conditions of ancient rivers (e.g., Hartley et al, 2015;Mahon and McElroy, 2018;Lyster et al, 2021Lyster et al, , 2022Hartley and Owen, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Bars are not explicitly captured at the experimental scales used to test theoretical and conceptual models about controls on bed-scale (e.g., Ganti et al, 2013;Leary and Ganti, 2020;Bradley and Venditti, 2021;Das et al, 2022) or landscape/channel-belt scale preservation (e.g., Heller and Paola, 1996;Martin et al, 2009;Paola et al, 2009;Straub and Wang, 2013;Hajek, 2015, 2019). Consequently, bar preservation is studied using field observations and remote imagery of modern systems (e.g., Dixon et al, 2018;Chamberlin and Hajek, 2019;Cardenas et al, 2020;Rahman, 2023) and numerical models (e.g., Kleinhans and van den Berg, 2011;Schuurman and Kleinhans, 2015;Nicholas et al, 2016;van de Lageweg et al, 2016bvan de Lageweg et al, , 2016aSambrook Smith et al, 2019;Li et al, 2023). These investigations have shown that channel-thread kinematics such as lateral migration, widening, thread-splitting, and confluence, influence the formation and morphology of bars in braided rivers (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Stable meandering rivers often form in rainforests [36]. Other factors, such as human activities [37,38], differences in the composition of embankments on both banks [39][40][41][42][43], and the slope of river basins or river beds, also have an important impact on river morphology [44,45]. These studies have made substantial progress in revealing the response of the main flow migration to changes in water and sediment conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Benefiting from the application of data and technology such as high-precision, ground-penetrating radar, and shallow seismic and dense well patterns, the study of braided river sedimentation (architecture) has transited from onedimensional lithofacies combination models (such as trench) and two-dimensional architecture unit combination relationships (such as outcrop profile) to three-dimensional space distribution models (such as ground-penetrating radar) [6][7][8]. Based on high-resolution satellite photos, the spatial observation scale of rivers has increased, and the study of river geomorphological characteristics has developed from local to overall [9][10][11][12][13]. In general, a lot of research has been carried out on braided river sedimentation, and the sedimentary architecture patterns of several braided river examples have been established [7,[14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%